Fast feedback - Tulgan, Bruce (HRD Press, 1999)
FAST stands for Frequent, Accurate, Specific and Timely, and FAST Feedback is a new approach to performance evaluation in sync with today's fast-paced, rapidly changing workplace. FAST can be used in conjunction with or as an alternative to six and twelve month reviews. FAST links training directly with ongoing performance evaluation by keeping employees in a constant feedback loop. There are many ways to implement FAST Feedback in your organization, including the customizable forms included in this pocket guide. This top selling title from renowned author Bruce Tulgan is appropriate for all supervisors, managers, executives, and educators.